Myanmar Agricultural Performance Survey (MAPS) dry season 2023: Agricultural input markets, credit and extension services - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2023)
This note provides an overview of agricultural input access and utilization for the post-monsoon (dry season) 2023 based on a nationally and regionally representative sample of 5001 crop farmers undertaken in June – July 2023. Most farmer input use decisions were taken prior to damage inflicted by Cyclone Mocha. Key findings • Access to mechanization services, tractors and combine harvesters (or threshers for pulses) was similar to the previous post-monsoon season and even showed recovery in most conflict areas. • In contrast to mechanization, access to seed was reduced in conflict areas. Almost half of all seed purchases nationally are made from neighboring farmers, indicating an opportunity to target extension to local informal seed producers to ensure quality. • Fertilizer application rates increased by 33 percent, driven especially by higher rates of urea application in response to higher paddy prices. The benefit-cost ratio of urea application to paddy crops averaged 2.09 at the urea sales price reported by agri-input dealers and 1.76 at farmer reported prices. The difference in reported prices likely reflects interest charges and local transport costs from the dealer to the farm. • Labor hiring by farmers increased in a tight rural labor market, resulting in wage increases averaging 1,000 MMK per day. The gap between male and female wages narrowed, especially in conflict areas. • Extension access deteriorated noticeably from a year ago. In-person extension services from public, private and NGO sources declined for cereals, oilseeds, and pulses, with the exception of private extension for groundnut. NGO extension services were sharply reduced and almost non-existent for some crops. Spatial analysis of extension access indicates that conflict is an important factor in extension access, pointing to an important role for improvements in mobile extension services. Yet increases in mobile extension access were modest and are unlikely to have compensated for the reduction in field extension agent access. • The share of farmers using credit changed little compared to the year before, but sources of credit did change. The share of farmers taking credit from Myanmar Agricultural Development Bank (MADB), microfinance institutions, private banks and money lenders all fell, while the share receiving credit form agricultural input retailers more than doubled. Recommendations • Improvements in the geographical coverage and content of mobile extension services could play an important role in offsetting reductions in in-person extension access. This is an opportunity for development partners to have a positive impact without increasing risk to beneficiaries or implementing partner staff. • The prevalence of local farmers as a seed source indicates that mobile extension services targeting informal seed producers could be important, along with facilitating access to certified seed for multiplication. • As nearly all chemical input distributors and machinery service providers depend on imports, access to foreign exchange is critically important.